New Trends in Tissue Engineering and Regenerative Medicine Official Book of the Japanese Society for Regenerative Medicine - Hibi, Hideharu; Ueda, Minoru (IntechOpen, 2014)
This book is an edited collection of all the achievements of the main members of the Dental Division of the Japanese Society for Regenerative Medicine, which derives from the Japanese Forum for Regenerative Dentistry established in 2003. Scientific meetings held by these organizations gleaned specific experiences of the academic community as well as clinical experiences of the most renowned experts in the field of dentistry. The editors are especially proud of bringing together leading biologists and dentists of all specialties. This unique collection of reports on the achievements and experiences of experts from all over the world represents the current spectrum of possibilities in tissue engineering of substitutes not only in dentistry but also in medicine. This book has been produced and distributed with the support from The Japanese Society for Regenerative Medicine.